Uterus transplants and Mexico’s rule of law - Palacios-González, C; Mendoza Cárdenas, HA (Oxford University Press, 2024)
Uterus transplantation is a new fertility treatment for some women who lack a functioning uterus. The number of countries where these transplants are performed has steadily increased, and in Mexico, there is a growing interest in this procedure among patients, researchers, and clinicians. In this paper we look at Mexico and its legal system in order to determine what is the legal status of uterus transplants, and whether there is a right to them according to Mexican legislation. To achieve this objective, we have organized this paper into four sections. First, we present a brief synopsis of what uterus transplants entail. Second, we carry out a historical overview of uterus transplants in Mexico. Third, we present the federal laws and regulations that apply to uterus transplants in Mexico. Finally, we defend that under Mexican legislation there is a positive right to uterus transplants. We substantiate the former by focusing on the right to the protection of health and the right to family making.